To determine the inverse variation equation, we use the formula:
p = k/q
where k is the constant of variation.
Given that p = 12 when q = 9, we can substitute these values into the equation to find k:
12 = k/9
Multiplying both sides by 9, we have:
108 = k
So the inverse variation equation is:
p = 108/q
To find p when q = 6, we substitute this value into the equation:
p = 108/6
Calculating this, we get:
p = 18
Therefore, when q = 6, p is equal to 18.
suppose that p and q vary inversely and p=12 when 9=3. Find p when q=6
1 answer